The extent of public awareness, understanding and use of the Global Solar UV index as a worldwide health promotion instrument to improve sun protection: Protocol for a systematic review - Lehmann, Maria; Heinitz, Maria; Uter, Wolfgang; Pfahlberg, Annette Bettina; Gefeller, Olaf (BMJ Open, 2019)
Introduction: (Over)exposure to ultraviolet radiation is a major risk factor for skin cancer. The Global Solar Ultraviolet Index (UVI) was introduced by the WHO and partner organisations in 1995 as a simple measure of the intensity of solar UV radiation, providing guidance for the population to use appropriate sun protective measures. Little is known about the impact of the UVI on actual sun protection behaviour. Our systematic review aims to assess global levels of awareness, understanding and use of the UVI as prerequisites for the preventive effectiveness of this public health tool. Methods and analysis: Systematic searches will be performed in 10 electronic literature databases including Medline, Scopus and Web of Science-Core Collection, two clinical trials registries and at least two grey literature databases (OpenGrey, Bielefeld Academic Search Engine). Additional literature sources will be retrieved using hand search of reference lists of included studies and snowballing methods. We will include studies with all types of quantitative study designs and participants reporting on at least one outcome in the three main categories (i) awareness, (ii) understanding and (iii) use of the UVI. We will assess the risk of bias within studies with an abbreviated version of the AXIS tool, designed specifically for cross-sectional studies. As we expect large heterogeneity in outcomes, we will conduct a narrative synthesis of results instead of a meta-analysis. Ethics and dissemination: Ethical approval and patient consent are not required as this is a systematic review based on published studies. The results of this study will be published in an international peer-reviewed journal.
CRIS-Team Scopus Importer:2019-07-23
Keywords: attitudes; health knowledge; health promotion; practice; public health; ultraviolet rays/adverse effects